2017
DOI: 10.1080/10715762.2017.1289377
|View full text |Cite
|
Sign up to set email alerts
|

The role of peroxiredoxin 6 in neutralization of X-ray mediated oxidative stress: effects on gene expression, preservation of radiosensitive tissues and postradiation survival of animals

Abstract: Peroxiredoxins are redox-sensing multifunctional enzymes, among them peroxiredoxin 6 (Prx6) can neutralize the most broadest range of hydroperoxides and play an important role in maintaining the redox homeostasis of the cell. In the present study, radioprotective and signaling regulatory effects of Prx6 were demonstrated and characterized. Intravenously administered exogenous Prx6 protects the organism of mice from the destructive action of ionizing radiation in the lethal dose range of 5-10 Gy. Dose reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 64 publications
0
28
0
2
Order By: Relevance
“…Previously, it has been shown that Prx1, Prx2, Prx5 and Prx6 are potent DAMPs in ischemic stroke, with TLR4 being their main recognition receptor. Through interaction with the TLR4 receptor, peroxiredoxins (Prx1, Prx2, Prx5 and Prx6) express pro-inflammatory/regenerative factors via the TLR4/MyD88/NF-kB signaling pathway [ 14 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. Moreover, we suggest that intravenous injection of recombinant Prx1 or Prx2 in animals before renal I/R injury can provide a preconditioning effect, through stimulation of the TLR4/NF-kB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, it has been shown that Prx1, Prx2, Prx5 and Prx6 are potent DAMPs in ischemic stroke, with TLR4 being their main recognition receptor. Through interaction with the TLR4 receptor, peroxiredoxins (Prx1, Prx2, Prx5 and Prx6) express pro-inflammatory/regenerative factors via the TLR4/MyD88/NF-kB signaling pathway [ 14 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. Moreover, we suggest that intravenous injection of recombinant Prx1 or Prx2 in animals before renal I/R injury can provide a preconditioning effect, through stimulation of the TLR4/NF-kB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…To test the therapeutic effect of exogenous Prx1 and Prx2 proteins, the solution of the corresponding recombinant protein was injected into the tail vein to a final concentration of 20 μg/g of bodyweight 15 min before the beginning of ischemia. Selection of the injection method and the concentrations of protein solutions was carried out according to previous studies [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant proteins harbored His-tag, so the enzymes were purified by affinity chromatography on Ni-NTA-agarose (Thermo Fisher Scientific, USA), according to the manufacturer's recommendations. The technique of protein isolation was described earlier [23]. According to electrophoresis in 12% SDS-PAAG, the purity of the obtained enzymes was at least 98%.…”
Section: Animals Diabetes Model and Peroxiredoxinmentioning
confidence: 99%
“…Кардиопротекторный эффект подтверждался нормализацией частоты сердечных сокращений, поддержанием контрактильной функции миокарда и предупреждением губительного действия окислительного стресса. Благодаря снижению уровня окисли-тельного стресса у мышей (индуцированного ионизирующим излучением в летальных дозах 5-10 Гр) посредством внутривенного введения экзогенного пероксиредоксина-6 был продемонстрирован радиопротекторный эффект [48]. Значение фактора изменения дозы составило 1,45.…”
Section: Av Maksimenko Approximation Of New Generation Pharmacologiunclassified